Evaluation of rubbercrete based on ultrasonic pulse velocity and rebound hammer tests - Mohammed B.S.; Azmi N.J.; Abdullahi M. (2023)
Several research works have been carried out to study the fresh and hardened properties of concrete containing crumb rubber (rubbercrete) as a replacement of fine aggregate. The outcomes of these studies have highlighted the advantages and disadvantages of rubbercrete compared with conventional concrete mixtures. In view of the fact that rubbercrete is being used in the construction industry for a variety of purposes, evaluations of the rubbercrete mixtures using non-destructive tests such as rebound hammer (RH) and ultrasonic pulse velocity (UPV) to establish valid relationships is worthwhile. Fifteen mixtures with different w/c ratios (ratios of weight of water to weight of cement) and crumb rubber content percentages were prepared, cast and tested using RH and UPV at different curing ages. Models were proposed and statistically validated to predict the relationship between compressive strength with UPV and rebound number (RN) for rubbercrete mixtures at 3, 7 and 28 days. 2010 Elsevier Ltd. All rights reserved.